Sosialisasi Kinesiologi Olahraga Pada Pembelajaran PJOK Anak Sekolah Dasar - Heni Yuli Handayani; Septyaningrum Putri Purwoto; Haryo Mukti Wibowo; Fajar Hamdhan Utama (Jurnal Abdi Masyarakat Kita, 2022)
Kinesiology is the study of movement. Sports kinesiology is very important for elementary school children and requires teacher assistance in the scope of education. Movement science in learning at school is given in physical education lessons, sports, and health (Penjasorkes). The kinesiology learning model is generally chosen by physical education teachers, not least at the elementary school level. This dedication to socializing sports kinesiology in PJOK learning was successful. This is because it makes students understand more about sports kinesiology in PJOK learning for elementary school children. Through this socialization activity, Movement learning in PJOK must pay attention to the characteristics of elementary school children. In addition, this socialization makes students understand efficient movement, effective movement and avoid injury in PJOK learning.